2021
DOI: 10.1186/s13059-021-02377-0
|View full text |Cite
|
Sign up to set email alerts
|

Using high-throughput multiple optical phenotyping to decipher the genetic architecture of maize drought tolerance

Abstract: Background Drought threatens the food supply of the world population. Dissecting the dynamic responses of plants to drought will be beneficial for breeding drought-tolerant crops, as the genetic controls of these responses remain largely unknown. Results Here we develop a high-throughput multiple optical phenotyping system to noninvasively phenotype 368 maize genotypes with or without drought stress over a course of 98 days, and collected multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 81 publications
0
51
0
1
Order By: Relevance
“…Bonferroni assumes each tested SNP is independent, but the presence of LD between SNPs makes that assumption incorrect and overly stringent. Previously, a similar threshold set was being widely used in other species, such as maize and Arabidopsis ( Wen et al, 2014 ; Wu et al, 2021 ; Zhu et al, 2021 ). Candidate gene lists were obtained from the 10-kb interval of the peak GWAS SNP.…”
Section: Methodsmentioning
confidence: 99%
“…Bonferroni assumes each tested SNP is independent, but the presence of LD between SNPs makes that assumption incorrect and overly stringent. Previously, a similar threshold set was being widely used in other species, such as maize and Arabidopsis ( Wen et al, 2014 ; Wu et al, 2021 ; Zhu et al, 2021 ). Candidate gene lists were obtained from the 10-kb interval of the peak GWAS SNP.…”
Section: Methodsmentioning
confidence: 99%
“…The imputed 1.2 M-SNP data based on the 1,001 Arabidopsis Genomes project filtered with cross-validation accuracy over 0.95 was used for mapping ( Arouisse et al, 2020 ). As the Bonferroni threshold is too stringent for quantitative gene identification, the genome-wide threshold of significance in this study was set to 8.10 × 10 −7 (1/ N , with N = 1,235,164 for the number of SNPs used in GWAS), as widely used in other work based on the same Arabidopsis population and in other species ( Lander and Kruglyak, 1995 ; Wen et al, 2014 ; Kooke et al, 2016 ; Wu et al, 2021) . The resulting SNPs with P -values less than the threshold were assigned to the same group if their inter-genomic distance was ˂20 kb.…”
Section: Methodsmentioning
confidence: 99%
“…Novel image-based feature or derived secondary traits have the power to decipher the complex genetic architecture of drought tolerance in maize (Wu et al, 2021) and can improve genome selection (GS) models. A good example is spectral reflectance data collected using a handheld multi-spectral radiometer: such secondary traits can improve the prediction accuracy by 20% for grain yield and 12% for grain protein content of spring wheat, which showed that combining HTP and genome selection in a plant breeding program could potentially improve the genetic gain by increasing the selection accuracy and reducing the breeding cycle time (Sandhu et al).…”
Section: State-of-the-art Technology and Applications In Crop Phenomicsmentioning
confidence: 99%